"Ye Double‐Minded": Black Parishioners' Attitudes toward Nonaffirming Church Climates. Issue 1 (24th January 2023) - Young, Luther
Abstract: Homophobia in the black community has been largely attributed to the Black Church's conservative views concerning sexual orientation. Prior research demonstrates that black congregations are generally nonaffirming of nonheterosexuality; however, few studies have investigated black congregants' responses to their churches' climates regarding sexuality. Using in‐depth interviews, this paper examines the extent to which black Christians are content with their congregations' nonaffirming climates. Findings indicate that although some black parishioners are content with or indifferent to their churches' climates, most respondents advocate for a change in how their congregations address sexual orientation, specifically calling for open conversations about sexuality. Furthermore, an examination of the language respondents used to evaluate congregational climates suggests discussions of sexuality in churches that humanize and encourage empathy for nonheterosexual identities may help facilitate such conversations. These results challenge assumptions of ideological homogeneity within religious organizations and could inform strategies to promote nonheterosexual inclusion in congregations.